1979
DOI: 10.1530/jrf.0.0560119
|View full text |Cite
|
Sign up to set email alerts
|

Proteins in the uterine secretions of the cow

Abstract: Summary. Cows of normal reproductive history were treated with progesterone for periods of 2\p=n-\3months. The uterine secretions yielded 5 major fractions of macromolecular components. Two of the fractions comprised serum proteins. In the other 3 fractions at least 9 non-serum proteins were observed, 7 in one fraction, but in only small amounts. Of the remaining 2 non-serum proteins one is an acid phosphatase recoverable in small amounts, and the other is lactoferrin and is the major non-serum protein present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The function of this protein is to transport iron from the endometrium to the conceptus (Chen et al, 1975 ;Roberts et al, 1986) (Roberts and Parker, 1974). However, specific uterine proteins have been described in cows (Roberts and Parker, 1974 ;Laster, 1977 ;Dixon and Gibbons, 1979) and in sheep (Roberts G. P. et al, 1976;Staples et al, 1978). Up to now, none of these proteins have been isolated and purified.…”
Section: Introductionmentioning
confidence: 99%
“…The function of this protein is to transport iron from the endometrium to the conceptus (Chen et al, 1975 ;Roberts et al, 1986) (Roberts and Parker, 1974). However, specific uterine proteins have been described in cows (Roberts and Parker, 1974 ;Laster, 1977 ;Dixon and Gibbons, 1979) and in sheep (Roberts G. P. et al, 1976;Staples et al, 1978). Up to now, none of these proteins have been isolated and purified.…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Ax [20] have reported that the concentrations of GAGs per 100 mg of protein identified from flushing of bovine oviduct and uterine horn are 9 and 20 mg/ml, respectively. The total protein concentrations for oviductal and uterine fluid are 1.2-52.0 [52,53] and approximately 10.0-18.6 mg/ml, respectively [54,55]. Therefore, the total GAG concentration in oviductal and uterine fluid is estimated at approximately 0.1-4.7 and 2.0-3.7 mg/ml, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the Pinduced uterine milk proteins accumulate in the uterine lumen of ewes and cows in significant amounts only after prolonged P exposure [7,11], suggesting that a similar scenario may be true for RBP. In addition to RBP, lactoferrin is another bovine endometrial transport protein that is regulated by P [4].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, since conceptuses of large domestic farm animals undergo noninvasive epitheliochorial placentation and the uterine epithelium is never eroded during pregnancy, uterine secretions may be required for nutritional support of the conceptus throughout gestation [1]. For this reason, uterine secretions of cattle [3][4][5][6][7][8], sheep [9][10][11][12], and pigs [13][14][15][16][17] have received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation